Phylogenetics and infrafamilial classification of Commelinaceae (Commelinales). (21st August 2021) - Lee, Chung-Kun; Fuse, Shizuka; Poopath, Manop; Pooma, Rachun; Tamura, Minoru N
Abstract: The morphologically diverse Commelinaceae consist of 41 genera with c . 650 species. Previous phylogenetic studies have revealed paraphyly of some taxa, but some of the infrafamilial taxa and most of the genera remain to be tested. To investigate phylogenetic relationships of the infrafamilial taxa and to test their monophyly, likelihood and Bayesian analyses with partial rbcL, matK and accD sequences were performed using 75 species from 33 genera of primarily eastern and south-eastern Asian Commelinaceae, with members of Haemodoraceae and Hanguanaceae as outgroups. The analyses resolved the early-diverging lineages of Commelineae and supported the monophyly of Dichorisandrinae and non-monophyly of Amischotolype, Belosynapsis, Murdannia, Pollia and Aneilema . Based on phylogenetics and morphology, we suggest that Palisotinae and Streptoliriinae should be raised to tribal rank, establishing subtribes Cochliostematinae, Commelininae and Murdanniinae, whereas Porandra, Belosynapsis, Anthericopsis are synonymized under Amischotolype, Cyanotis and Murdannia, respectively. Rhopalephora and two Australian Pollia spp. are moved to Aneilema. With all aforementioned taxonomic additions and changes, we propose a new classification for Commelinaceae, consisting of two subfamilies, six tribes, seven subtribes and 37 genera.